History of development of marine science at the Escuela de Biología, Universidad de Costa Rica - Cortés, Jorge (2009)
La Escuela de Biología (School of Biology) of the Universidad de Costa Rica has contributed significantly to the advancement of marine sciences in Costa Rica. It has done this through the education of students, and together with the Centro de Investigación en Ciencias del Mar y Limonología (Marine Sciences and Limnology Research Center) (CIMAR) with the generation of knowlegde on marine organisms, ecosystems and processes in Costa Rica.